Confidentiality assurance in Multi-agent Robotic System - et. al., Zakoldaev D. A., (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, the authors consider the feasibility of using quantum encryption in a multi-agent robotic system. The authors consider examples of such systems, describe the functional structure of the system in question, describe the scheme for ensuring information security. Finally, the authors see the use of quantum cryptographic algorithms appropriate for resolving the issue of confidentiality in multi-agent robotic systems and believe that this method has the potential for further scientific developments in the field of security in multi-agent robotic systems.